(untitled) (E Conference Zone, 2022)
The article gives information about how to define “you” in your relationships; about why getting along with people is not always easy; about the various ways people relate to each other – at home, at school, at work, and at even within their communities; about how relationships develop and of course about the importance of relationships. On top of that, it deals with the fact that coping with the ups and downs of friendship helps you to learn about yourself and others.